2019
DOI: 10.1177/0300060519879580
|View full text |Cite
|
Sign up to set email alerts
|

The p48_HPC antithrombogenic flow diverter: initial human experience using single antiplatelet therapy

Abstract: The p48 is a low-profile, intermediate-porosity flow diverter. phenox GmbHtrademarked hydrophilic polymer coating (pHPC) is a hydrophilic coating that has been shown in vitro to reduce the thrombogenicity of nitinol device surfaces. We performed the present study to determine whether the p48_HPC can be implanted using prasugrel alone. Methods: We retrospectively identified all patients who were treated with the p48_HPC from January 2017 to December 2018 (n ¼ 5) and underwent single antiplatelet therapy (SAPT) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 27 publications
2
28
0
Order By: Relevance
“…pHPC has no pharmaceutical effect, is biocompatible with no evidence of acute inflammatory response, and does not interact with the physical properties of the metallic implant [10,11]. Bhogal et al [5] recently reported on the use of the p48MW HPC under SAPT in treating five patients with unruptured aneurysms and reported no thromboembolic complications, with just one patient experiencing a minor hemorrhage from the treated aneurysm 2 weeks postoperatively. However, only prasugrel was used for SAPT, and there were no ruptured aneurysms treated in this series.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…pHPC has no pharmaceutical effect, is biocompatible with no evidence of acute inflammatory response, and does not interact with the physical properties of the metallic implant [10,11]. Bhogal et al [5] recently reported on the use of the p48MW HPC under SAPT in treating five patients with unruptured aneurysms and reported no thromboembolic complications, with just one patient experiencing a minor hemorrhage from the treated aneurysm 2 weeks postoperatively. However, only prasugrel was used for SAPT, and there were no ruptured aneurysms treated in this series.…”
Section: Discussionmentioning
confidence: 99%
“…Its hydrophilic polymer coating (pHPC, phenox, Bochum, Germany) is a novel glycan-based multilayer polymer that has been shown to have significant anti-thrombogenic properties when tested in vitro [4]. A recently published study concluded that the p48MW HPC appears both safe and efficacious under single antiplatelet therapy (SAPT) using prasugrel in selected cases of unruptured aneurysms [5]. However, no publications have yet focused on the use of this surface-modified FDS in the setting of aSAH.…”
Section: Introductionmentioning
confidence: 99%
“…Bhogal et al reported the use of the p48MW HPC in treating five patients with unruptured aneurysms using only prasugrel as SAPT. They reported no thromboembolic complications while one patient experienced a minor hemorrhage from the treated aneurysm 2 weeks postoperatively 30…”
Section: Discussionmentioning
confidence: 97%
“…The reported experience with the p48 MW Flow Modulation Device is still very limited (Bhogal et al, 2019 ; Bhogal et al, 2020 ; Aguilar-Perez et al, 2020 ). The Buenos Aires experience with the uncoated version based on 25 patients with 25 aneurysms reported an adequate occlusion rate of 79.2% and a procedure-related complication rate of 4% with no permanent morbidity (Bhogal et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%